Documentary Objects, Textual Materials, and Performative Testimony in Memory Reconstruction – Mi vida después (2009) by Lola Arias - Cobello, Maria Denise (2025)
Mi vida después by Lola Arias premiered in 2009 in Buenos Aires, as a stage proposal about people who reconstruct their childhood experiences and the life stories of their parents, some of them disappeared because of the repressive State that organized and executed the most atrocious dictatorship in Argentine history between 1976-1983. In this paper, we inquire about the use of documentary materials on stage, the fgure of the witness, and the value given to testimony. We postulate that this stage experience develops procedures that give shape to a dramaturgy of the living based on performative testimony that allows new approaches to the memories presented in the public sphere as proof of truth. The documents and testimonies emerge from the representational gap that opens up between the generation of the parents who suffered censorship and repression and the generation of the young performers who can give an account of their childhood memories. From their stories, one can see the lack, the absence, the emptiness, and the diffculties in speaking. These forms of expression function as dual discursive devices that express both subjective experience and the refection of a political and social dimension.